Effect of microwave argon plasma on the glycosidic and hydrogen bonding system of cotton cellulose. (20th January 2017) - Prabhu, S.; Vaideki, K.; Anitha, S.
Highlights: Certain combinations of microwave Ar plasma process parameters improved the hydrophilicity of cotton fabric while certain other combinations reduced the same i.e., a single process gave rise to dual effect. Box-Behnken method was applied to optimize both the effects. ATR-FTIR analysis revealed the strain induced in each of the O6H⋯O3 inter chain hydrogen bond, O3H⋯O5, O2H⋯O6 intra chain hydrogen bond, CH⋯O inter sheet hydrogen bond and COC glycosidic covalent bond and rotation about C5 C6 covalent bond. ATR-FTIR analysis shows the lengthening of the flanking hydrogen bonds and rotation about C5 C6 covalent bond and lengthening of CH covalent bond in the sample for which hydrophilicity was maximized. Whereas, the ATR-FTIR analysis of the sample that exhibited minimum hydrophilicity revealed the lengthening and rotation of the O2H⋯O6 flanking hydrogen bond and C5 C6 covalent bond. The changes observed in the minimum hydrophilic sample were resisted by the shortening of the O3H⋯O5 intramolecular hydrogen bond and COC glycosidic bond and the change in the weak inter sheet CH⋯O bond length. These changes lead to the alterations in the unit cell parameters and also a decrease in crystallinity which was evident from XRD studies. FESEM analysis captured the etching effect of plasma. Thus, the synergism between the structural and physical changes induced by microwave Ar plasma process was responsible for the dual behavior. Abstract: Cotton fabric was processed with microwave (Ar) plasma to alter its hydrophilicity. The process parameters namely microwave power, process gas pressure and processing time were optimized using Box-Behnken method available in the Design Expert software. It was observed that certain combinations of process parameters improved existing hydrophilicity while the other combinations decreased it. ATR-FTIR spectral analysis was used to identify the strain induced in inter chain, intra chain, and inter sheet hydrogen bond and glycosidic covalent bond due to plasma treatment. X-ray diffraction (XRD) studies was used to analyze the effect of plasma on unit cell parameters and degree of crystallinity. Fabric surface etching was identified using FESEM analysis. Thus, it can be concluded that the increase/decrease in the hydrophilicity of the plasma treated fabric was due to these structural and physical changes.